121 Autoimmune autonomic neuropathy on the Adie spectrum: 'Ross syndrome?'. Issue 6 (27th May 2022) - Basgaran, Amedra; McColgan, Peter; Sacks, Benjamin; Oommen, Grace; Koay, Shiwen; Alsukhni, Rana; Hagen, Ellen Merete; Ingle, Gordon; Iodice, Valeria; McNamara, Patricia
Abstract : Ross syndrome is a rare syndrome of segmental autonomic dysfunction, characterised by a triad of tonic pupils, hyporeflexia and anhidrosis. We present an atypical case of such a patient, presenting with added features of cardiovascular autonomic dysfunction. Our case concerns a 66-year-old female, who experienced progressive stepwise deterioration in the functionality of her autonomic nervous system. Her symptoms began with a left Adie's pupil, followed by a chronic dry cough and diarrhoea. The onset of anhidrosis and orthostatic hypotension subsequently occurred 30 and 40 years later, respectively. Autonomic function testing confirmed cardiovascular autonomic failure as well as deficiencies of sudomotor, salivary and tear function. Severe orthostatic hypotension was demonstrated along with an abnormal Valsalva response, and loss of the nocturnal circadian rhythm. Thermoregulatory and dynamic sweat testing further confirmed global anhidrosis. Our case highlights that patients do not always fit diagnostic criteria of eponymous syndromes, and usually demonstrate varying levels of autonomic dysfunction. We propose diagnosis of such atypical cases to be part of an Adie spectrum ganglionopathy, rather than attempting to fit into an eponymous syndrome phenotype. We further believe there to be an autoimmune basis to the Adie spectrum of disorders and have proposed immunotherapy as definitive management. a.basgaran@nhs.net|ABN Bursary